Óleo essencial de Cantinoa carpinifolia Benth.: composição química e estudo do mecanismo de ação sobre Escherichia coli e Staphylococcus aureus - Camargo, Karen Caroline (2018)
The present work sought to characterize the essential oil from Cantinoa carpinifoliaBenth. to evaluate its antibacterial potential and to performa preliminary study of its mechanism of action against Escherichia coliand Staphylococcus aureus. The extraction of the essential oil was accomplished by the hydrodistillation technique, using a modified Clevenger apparatus. The chemical characterization was achieved by means of a gas chromatograph coupled to a mass spectrometer, and the compounds were quantified by gas chromatography with a flame ionization detector. The antibacterial activity wasevaluated by the macrodilution technique, wherein the time necessary for cell death was determined. The mechanism of antibacterial action was studied by means of tests based on the evaluation of the permeability (potassium efflux and salt tolerance) and integrity (release of cellular materials) of the bacterial cell membrane, as well as determination of the effects on the surface of the cells by Scanning Electron Microscopy (SEM). The principal constituents that characterized the essential oil of C. carpinifoliawere the monoterpenes α-tujone (38.14%), β-tujone (22.43%), sabinene (5.00%) and cis- pinocanphene (5.55 %) and the sesquiterpene β-caryophyllene (7.28%). Bactericidal and bacteriostatic activities against E. coli and S. aureus, respectively, were observed at essential oil concentrations of 6.25 and 0.39 μL mL -1 . The bacterial strains were completely inactivated after 135 (E. coli) and 197 min (S. aureus). No efflux of potassium or extravasation of cellular materials was observed upon treatment with the essential oil. In addition, there was no change in salt tolerance. By means of electromicrographs it was possible to perceive the harmful effects on both bacteria, although the rupture of the cellular membrane could not be observed. Thus, the essential oil from C. carpinifoliapresented biological activity against the evaluated bacterium; however, it did not cause damage to the cell membranes of E.coliand S. aureusin any of the tests performed.